Impact of social entrepreneurship on sustainable regional development - Miroslav Mihaylov (Journal of Research and Innovation for Sustainable Society)
Throughout its historical development, humanity has always strived to create a sustainable and just economy. In addition to ensure market stability, the core idea of the "social economy" is to build an economic system that respects human dignity, promotes social justice, and contributes to public welfare. All of this remains merely an utopian theory if enterprises do not achieve positive financial results and produce goods and services that are beneficial to society. Social enterprises are an important part of the European economic and social system. They represent more than 160,000 enterprises across Europe, owned by 123 million individual members, and provide employment to 5.8 million citizens1 . Their impact varies in each European region and depends on the development of the civic economy. In this study, we will examine the historical development of social enterprises in Europe and Bulgaria. We will attempt to present their influence in two regions, utilizing different quantitative and qualitative indicators. By analyzing some of the challenges facing the civic economy and exploring funding opportunities, we will strive to determine their development prospects.